Joule Heating Effect on the Coupling of Conduction with Magnetohydrodynamic Free Convection Flow from a Vertical Flat Plate - Alim, M. A. A.; Alam, Md. M. M.; Al-Mamun, Abdullah (Nonlinear Analysis: Modelling and Control, 2007)
The present work describes the effect of magnetohydrodynamic (MHD) natural convection flow along a vertical flat plate with Joule heating and heat conduction. The governing boundary layer equations are first transformed into a non-dimensional form and resulting nonlinear system of partial differential equations are then solved numerically by using the implicit finite difference method with Keller box scheme. The results of the skin friction co-efficient, the surface temperature distribution, the velocity and the temperature profiles over the whole boundary layer are shown graphically for different values of the Prandtl number Pr (Pr = 1.74, 1.00, 0.72, 0.50, 0.10), the magnetic parameter M (M = 1.40, 0.90, 0.50, 0.10) and the Joule heating parameter J (J = 0.90, 0.70, 0.40, 0.20). Numerical values of the skin friction coefficients and surface temperature distributions for different values of Joule heating parameter have been presented in tabular form.